2017
DOI: 10.1021/acsami.7b10668
|View full text |Cite
|
Sign up to set email alerts
|

From Chlorella to Nestlike Framework Constructed with Doped Carbon Nanotubes: A Biomass-Derived, High-Performance, Bifunctional Oxygen Reduction/Evolution Catalyst

Abstract: The development of effective bifunctional catalysts for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) is significant for energy conversion systems, such as Li-air batteries, fuel cells, and water splitting technologies. Herein, a Chlorella-derived catalyst with a nestlike framework, composed of bamboolike nanotubes that encapsulate cobalt nanoparticles, has been prepared through a facile pyrolysis process. It achieves perfect bifunctional catalysis both in ORR and OER on a single cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 74 publications
(103 reference statements)
1
38
0
Order By: Relevance
“…Similarly, all kinds of biowaste have been carbonized and used as host materials in the cathodes of lithium–sulfur, lithium–selenium, or lithium–oxygen batteries. Within recent years, for example, carbons made from waste materials such as fruit stones or peels, algae, nutshells, soybean hulls, grain waste, other plant waste, saw dust, and lignin have been described in this regard.…”
Section: Electrodesmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, all kinds of biowaste have been carbonized and used as host materials in the cathodes of lithium–sulfur, lithium–selenium, or lithium–oxygen batteries. Within recent years, for example, carbons made from waste materials such as fruit stones or peels, algae, nutshells, soybean hulls, grain waste, other plant waste, saw dust, and lignin have been described in this regard.…”
Section: Electrodesmentioning
confidence: 99%
“…Carbons made from biomass often naturally benefit from nitrogen doping due to the presence of nitrogen in many bioresources and are thus especially appealing. In cases where N‐doping from the carbon precursor is not sufficient, other nitrogen containing precursors like melamine, which can be synthesized from sustainable resources, may be added before carbonization . To decrease the overpotential and increase the efficiency of the ORR/OER, biomass‐based carbons may also be impregnated with metal ions or particles .…”
Section: Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Together these results indicate that CoO indeed exits in catalysts of CoNASS, which could function to enhance the electron transfer and ORR performance. 46,47 To further investigate the contents and chemical states of the elements in the as-prepared carbon samples, XPS was conducted ( Fig. S4 †).…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…Biomass materials are the ideal carbon precursor for synthesizing ORR catalysts due to their renewability and large-scale and low-cost production [18][19][20][21][22][23][24][25]. Recently, several studies reported biomass-derived ORR catalysts with efficient catalytic activities.…”
Section: Introductionmentioning
confidence: 99%